A Shared Diagnostic Stewardship Approach toward Improving Autoimmune Encephalopathy Send-out Testing Utilization. (24th November 2020) - Sharp, Cierra N; Fletcher, Anita; Muluhngwi, Penn; Snyder, James; Linder, Mark W; Jortani, Saeed A
Abstract: Background: For many laboratories, autoimmune encephalopathy (AE) panels are send-out tests. These tests are expensive, and ordering patterns vary greatly. There is also a lack of consensus on which panel to order and poor understanding of the clinical utility of these panels. These challenges were presented to our newly formed, multidisciplinary, diagnostic stewardship committee (DSC). Through this collaboration, we developed an algorithm for ordering AE panels; combining diagnostic criteria with practice guidelines. Methods: We analyzed test-ordering patterns in 2018 and calculated a true-positive rate based on clinical presentation and panel interpretation. An evidence-based approach was combined with input from the Department of Neurology to synthesize our algorithm. Efficacy of the algorithm (number of panels ordered, cost, and true positives) was assessed before and after implementation. Results: In 2018, 77 AE-related panels were ordered, costing 137 510. The true-positive rate was 10%, although ordering multiple, similar panels for the same patient was common. Before implementing the algorithm (January 1–July 31, 2019), 55 panels were ordered, costing 105 120. The total true-positive rate was 3.6%. After implementation, 23 tests were ordered in a 5-month period, totaling 50 220. The true-positive rate was 13%. Conclusion: With the DSC-directed mandate, we developed an algorithm for ordering AE panels. Comparison of pre- and postimplementation data showed a higher true-positive rate, indicating that our algorithm was able to successfully identify the at-risk population for AE disorders. This was met with a 43% decrease in the number of tests ordered, with total cost savings of 25 000 over 5 months.